Close-to-practice research: The need for student voice and the strange case of Academy x (UCL Press, 2020)
The idea that teaching and school leadership should be informed by research and other evidence has developed traction recently in England and other jurisdictions. Yet, such research has too seldomly involved the student perspective in leadership decision-making. This article presents a case study of an 'all through' academy in the south of England (Academy x) that attempted to address this issue through research that was close to practice in nature. Here, school leaders, teachers, parents and, specifically, disadvantaged male students' perspectives of barriers and enablers to their attainment were explored with a view to working collaboratively with these stakeholders to respond to the findings. However, we had not taken into account that the credibility of the students' perspectives and the nature of the messages emerging from the findings would be questioned, and would influence a decision by school leaders not to act upon them. We consider how these issues might be addressed if student voice as a form of close-to-practice research is to become a reality.